Perceived Social Responsibility and Vaccine Hesitancy Among Parents of Grade 12 Student in Laboratory High School - R.T Deximo; Enaguas G Lucero (Universitas Pendidikan Indonesia (UPI), 2021)
Concerns about vaccine hesitancy are growing worldwide, and now parents are also refusing to vaccinate their children because of vaccination issues even against vaccine-preventable diseases. Hence, this study was conducted to determine the level of vaccine hesitancy and perceived social responsibility in parents and their association with one another. The novelties in this research are (1) Level of Perceived Social Responsibility among Parents, (2) Level of Vaccine Hesitancy among Parents, and (3) Association between the Level of Perceived Social Responsibility and Level of Vaccine Hesitancy. In this study, a quantitative-descriptive research design was used to find out the level of acceptability among the 40 selected parents of Grade 12 students in Sultan Kudarat State University (SKSU) – Laboratory High School. A random sampling technique was utilized in this study. The results implied that the parents have a high level of perceived social responsibility. The results also showed that the parents have a low level of vaccine hesitancy. As to the test of the association between perceived social responsibility and vaccine hesitancy, it shows that there is a statistically significant association between them. Therefore, parents of Grade 12 students have a high level of perceived social responsibility and know that vaccinations are part of their responsibilities as citizens.